Pengaruh Pendidikan Kesehatan tentang Pemanfaatan Rambut Jagung sebagai Antidiabetes Terhadap Tingkat Pengetahuan Pasien Penderita Diabetes Mellitus - Mustapa, Firliyanti; Ilham, Rosmin; Zainuddin, Zainuddin (Yayasan Mandar Indonesia, 2025)
Diabetes mellitus remains one of the most widely recognized health problems worldwide, with highly diverse morbidity. Therefore, appropriate management and prevention efforts are required, one of which is improving patients’ knowledge through health education interventions using non-pharmacological approaches, such as herbal therapy derived from corn silk (Zea mays L.). This study aimed to determine the effect of health education on the utilization of corn silk as an antidiabetic agent on the knowledge level of patients with diabetes mellitus in Lito Village, Paguyaman Pantai District. This research employed a quantitative approach with a pre-experimental design using a one-group pre-test and post-test method. The sampling technique used was total sampling, involving 38 respondents. The instrument used was a questionnaire, supported by standard operating procedures (SOPs) and leaflet media. The results showed that before the health education intervention, 37 respondents (97.4%) had poor knowledge, while only 1 respondent (2.6%) had good knowledge. After the health education intervention, the respondents’ knowledge level increased, with 36 respondents (94.7%) demonstrating good knowledge and only 2 respondents (5.3%) remaining in the poor knowledge category. The paired sample t-test analysis yielded a p-value of 0.000 (α < 0.05). Therefore, it can be concluded that there is a significant effect of health education on the knowledge level of patients with diabetes mellitus.